Lapisan condensed section pada batulempung gampingan Nanggulan, Pegunungan Kulonprogo, DIY - nuraini, siti (ReTII, 2020)
Condensed section (cs) is defined as later stage of transgressive cycle which situated to the uppermost transgressive layer before reaching regressive phase of highstand systems tract (HST). This layer sometimes embraces to mfs (maximum flooding surface) as indicator of deepening depositional environment (Vail et all., 1984; Loutit et all., 1988). One of condensed section character is displayed by abundant glauconite minerals ((K, Na) (Fe3+, Al, Mg)2 (Si, Al)4O10 (OH)2) within fine grained lithology together with organic matters. These cs layer preserved in an oxidizing environment due to slow sedimentation process. In fact, within calcareous claystone of Nanggulan Formation is found accumulation of authigenic glauconite mineral. The purpose of this study to investigate condensed section (cs) character by microscopic observation of thin sections from Songgo and Watupuru of Nanggulan’s lithology. Basically, glauconite mineral shows spherical or ovoid shape, green color, dull or earthy luster, embedded to calcareous claystone and also filled larger benthonic foraminifera tests. Glauconite only encountered to the fine grain rocks (calcareous claystone) however none to the underlying or upperlying of cs layer itself in Nanggulan Formation (such as sandstone, conglomeratic sandstone or siltstone). If it presents there, very few and indicating a reworking process of altered clay and ferroan oxidic minerals. Condensed section in Nanggulan Formation merges with fossil layer of Nummulites djogyakartae (Mark, 1956) which is interpreted to be a key indicator of post transgressive event in depth approximately 20- 60 m (boundary of inner neritic to middle neritic). In other word, transgressive phase had ever happened during Nanggulan age (Middle Eocene) which caused a decreasing clastic sediment supply to the basin.